2014
DOI: 10.1007/s10157-014-1073-z
|View full text |Cite
|
Sign up to set email alerts
|

The level of urinary α1 microglobulin excretion is a useful marker of peritubular capillaritis in antineutrophil cytoplasmic antibody associated vasculitis

Abstract: PTC or arteriolitis occurs at a high rate independently of crescentic glomerulonephritis in ANCA-associated vasculitis patients. The levels of u-α1MG excretion reflect the degrees of tubular atrophy and interstitial fibrosis. Moreover, high levels of u-α1MG excretion suggest that PTC is more likely than arteriolitis in ANCA-associated vasculitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, tubulointerstitial nephritis with normal glomeruli in AAV have been described in the first renal biopsy with necrotizing and crescentic ANCA GN in the second renal biopsy thereafter [ 46 , 47 ]. These observations suggest that AAV is a small vessel vasculitis manifesting to glomerular (necrotizing and crescentic ANCA GN) and tubulointerstitial compartments (intimal arteritis), and that the characteristics of each manifestation are independent [ 48 ]. Based on our findings that complement components C3 and C4 indicate vasculitis manifestations to distinct renal compartments in ANCA GN, it is attractive to speculated that innate immunity facilitates kidney injury by pathomechanisms attributed to specific complement system components.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, tubulointerstitial nephritis with normal glomeruli in AAV have been described in the first renal biopsy with necrotizing and crescentic ANCA GN in the second renal biopsy thereafter [ 46 , 47 ]. These observations suggest that AAV is a small vessel vasculitis manifesting to glomerular (necrotizing and crescentic ANCA GN) and tubulointerstitial compartments (intimal arteritis), and that the characteristics of each manifestation are independent [ 48 ]. Based on our findings that complement components C3 and C4 indicate vasculitis manifestations to distinct renal compartments in ANCA GN, it is attractive to speculated that innate immunity facilitates kidney injury by pathomechanisms attributed to specific complement system components.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Under normal conditions, approximately 99.9% of the free α1-MG filtered freely through the renal glomerular basement membrane is reabsorbed by the proximal tubular cells. Any proximal tubular cell dysfunction could result in increased quantities of α1-MG in the urine, hence urinary α1-MG has been recognized as a sensitive marker for the early detection of tubular injury in many diseases, 3,4 especially in diabetic kidney disease in recent years. 5,6 Urinary α1-MG has been recommended by expert consensus on clinical diagnosis of diabetic nephropathy as an indicator to screen early tubular involvement in Chinese adults.…”
Section: Introductionmentioning
confidence: 99%
“…We sampled arterioles with inflammation and destructed internal elastic lamina and found large fibrotic foci, which could represent scarring originating from arteritis in the kidney biopsy. Ohashi et al 13 suggested that not only PTC, but also arteriolitis could play an important role in the pathogenesis of tubulointerstitial nephritis due to AAV. In our case, arteriolitis but not PTC was observed.…”
Section: Discussionmentioning
confidence: 99%